Solving the economic dispatch problem by using differential evolution - S. Khamsawang; P. Wannakarn; S. Pothiya; S. Jiriwibhakorn (My University, 2009)
This paper proposes an application of the differential evolution (DE) algorithm for solving the economic dispatch problem (ED). Furthermore, the regenerating population procedure added to the conventional DE in order to improve escaping the local minimum solution. To test performance of DE algorithm, three thermal generating units with valve-point loading effects is used for testing. Moreover, investigating the DE parameters is presented. The simulation results show that the DE algorithm, which had been adjusted parameters, is better convergent time than other optimization methods.
Keywords: Differential Evolution; Economic Dispatch; Electric Power System Optimization